Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah - Mey Lani Rumra; Fajar Satriya Segarawasesa (Financial and Accounting Indonesian Research, 2026)
This study aims to analyze the influence of the Regional Financial Accounting System, Utilization of Information Technology, Competence of Human Resources, and Internal Control System on the quality of financial reports of the local government of Southeast Maluku Regency. This study is a quantitative research. The population of this study is structural officials at the Work Unit of the Southeast Maluku Regency Government and sampling using purposive sampling. Data collection was carried out by distributing questionnaires to employees of the Regional Device Organization of Southeast Maluku Regency. The collected data were processed using SPSS. The results of hypothesis testing show that the Regional Financial Accounting System has a positive effect on the quality of financial reports, Utilization of Information Technology has no effect on the quality of financial reports, while Competence of Human Resources has an effect on the quality of financial reports and Internal Control System has an effect on the quality of financial reports of the local government.